Blood levels of pro- and anti-inflammatory cytokines in children after acute kidney injury at different stages of observation - Driianska, V.; Lavrenchuk, O.; Bagdasarova, I.; Fomina, S.; Kholod, V.; Nepomnyashchii, V. (Ukrainian Journal of Nephrology and Dialysis, 2022)
Identifying the factors for progression of kidney pathology after acute kidney injury (AKI) in children is important for making clinical decisions and creating strategies for the prevention and treatment of chronic kidney disease (CKD). The present study aimed to investigate the value of serum levels of tumor necrosis factor α (TNF-α) and transforming growth factor (TGF-β) as markers of CKD progression in children after AKI. Methods. In this cross-sectional cohort study, the levels of serum cytokines were studied in 63 children from 6 months to 18 years old who had undergone AKI and 10 healthy children (reference group) using ELISA. The peculiarities of those who recovered (n=14) and those who were subsequently diagnosed with CKD stage 1 ​ (n=22) or CKD stages 2-3 (n=27) were determined. An analysis was also carried out taking into account the duration from the episode of AKI: early recovery period up to 3 months (n=21), 3-12 months (n=9), 1-3 years (n=22), and more than 3 years (n=11). “SPSS for Windows. Version 11" - Student’s test or Mann-Whitney Rank Sum Test was used. The correlation analysis was determined using the Pearson (r) or Kendall/Spearman method (ρ). Results. An increase in serum levels of the anti-inflammatory but pro-sclerotic TGF-β was observed in all children convalescing with AKI regardless of disease progression, with mean levels of the indicator increasing in the delayed phase. An increase in TGF-β levels ≥40.5 pg/mL in the first 3 months after AKI was documented in patients with an unfavorable disease course, such that these patients could be classified as a risk group for the development of fibrotic complications. No peculiarities in mean serum levels of proinflammatory TNF-α were observed in children who had suffered AKI, and there was no significant difference when comparing the groups according to the consequences of the disease. In the individual analysis, it was found that after the 12th month of observation, a high TNF-α level (≥8.0 pg/ml) was associated with an increase in the proportion of patients with CKD 2-3 (p < 0.001), which can be used to predict disease progression. Conclusions. This study demonstrates the feasibility of determining serum levels of TNF-α and TGF-β in children with AKI, which could be used as potential predictors of CKD risk to optimize treatment and prevention.